Confidence Level of College Students' Learning Activity at University - Ismail, Adinda Sinta; Zainun, Zainun (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research was motivated by the low level of learning activity in students. The aim is to determine the level of self-confidence in active learning in students of the Faculty of Da'wah and Communication of the State Islamic University of North Sumatra whose research is based on indicators, namely believing in self-competence or ability, having good self-control, having an internal locus of control in responding, daring to accept and face the rejection of others and having a positive perspective on themselves. Students of the Faculty of Da'wah and Communication. Based on the problem under study, the method used in this research is descriptive with a quantitative approach. The population is all Faculty of Da'wah and Communication students in semester VI of 2020, with 460 students. The sample used is 25% of the total population, namely 115 students using the Stratified Random Sampling technique. Data collection using a questionnaire with 20 items deployed using a Google form. The data analysis technique used in this study uses statistical techniques using quantitative analysis. The data analysis technique used is scoring which is assisted by SPSS 27.00 and Microsoft Excel. The results revealed that the level of confidence in a learning activity in students of the Faculty of Da'wah and Communication of the State Islamic University of North Sumatra was in the medium category with a percentage of 44%. In comparison, the very low category was 5%, in the low category 20%, in the high category 23%, and in the very high category 7%.